Process Features Discovery Of LowPressure Layers - Abdirazakov Akmal Ibrahimovich; Axmedov Muxtor Muzaffarovich (Genius Journals, 2024)
This article provides information on the complexity of drilling into low-pressure formations and the use of balanced pressure drilling technologies during drilling, as well as the rate of displacement of the gas-liquid mixture and the causes of adverse effects.
Keywords: formation; pressure; liquid